(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this investigation was to study the effect ofextractive content on the wood sorption isotherms of six Sudanese hardwoodspecies i.e. Acacia nilotica, A.senegal, Anogeissus leiocarpus, Boswelliapapyrifera, Ailanthus excelsa and Calotropis procera growing in North andSouth Kordofan States. For each species, wood samples were collected fromsix trees, from which specimens were prepared. The effect of extractives onequilibrium moisture content was studied by comparing the equilibriummoisture content of hot water extracted and unextracted wood. Experimentalequilibrium moisture content values for extracted and unextracted specimenswere obtained at different levels of relative humidity. These specimens wereplaced in a closed desiccator, which contained saturated salt solution ordifferent concentrations of sulphuric acid to maintain relative humidity andthen kept in an oven at the specified temperature (60 ○C) until equilibriummoisture content was obtained. Desorption and adsorption isotherms of thesix wood species exhibited sigmoid curves. The results showed directrelationship between equilibrium moisture content and relative humidity thatcould be well explained by third-order polynomial functions. The effect ofextraction was significant at few relative humidity values in some species;unextracted wood had higher equilibrium moisture content than extractedwood.